Visual Communication Psychology in the Age of AI: An Audience Perception Analysis of Face Filters on TikTok Media - Razali, Geofakta; Ramonita, Latifa (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze audience perceptions of artificial intelligence (AI)-based facial filters in TikTok content, with a specific focus on the account Arbie Seo. Employing a quantitative survey approach with 20 respondents, the research explores the impact of AI filters on authenticity, credibility, visual appeal, as well as psychological effects and digital identity representation. Findings reveal that 75% of respondents believe AI filters contribute to the construction of new postmodern beauty standards, while 90% consider the use of filters as a form of self-presentation aligned with social media trends. Additionally, 50% of participants perceive AI filters as promoting unrealistic beauty ideals, and 100% agree that such filters affect the perceived authenticity and credibility of content. These results support the assumption that AI technologies shape visual perception not only aesthetically but also psychologically. Drawing on media determinism and postmodernism theories, the study explains how facial filters create simulations that blur the boundaries between reality and representation. The implications of this research highlight the importance of ethical AI implementation in digital communication strategies to preserve content authenticity and credibility within an evolving visual culture.